Nietzsche's Signpost for Feminism - (:unkn) unknown (My University, 2016)
This paper focuses on the apparent misogyny and anti-feminism found in Part VII of Nietzsche’s Beyond Good and Evil (BGE). Following an interpretation put forward by Maudemarie Clark, I argue that Nietzsche’s claims and observations about women are purposely reflective of the dubious metaphysical assumptions of dualism and essentialism maintained with respect to biological sex. Given this, we can see Nietzsche’s text as highlighting the effects of “cultural breeding” in the form of gender. Thus, this paper aims to rehabilitate Nietzsche’s characterizations of women and “woman’s emancipation” as an important signification of the culturally bred, latent discrimination of the sexes, which appears to be exposed later in Simone de Beauvoir’s, The Second Sex (and continues to be remedied today). This interpretation may deliver Nietzsche’s text as an invitation for movement towards the pursuit of a radical transgression of conventional classifications of sex and gender.
Keywords: Feminism; Gender; Misogyny; Nietzsche; Sex Essentialism; Women